A new genus and species of basal horntail (Hymenoptera, Siricidae) from the Lower Cretaceous of China. (November 2018) - Wang, Mei; Rasnitsyn, Alexandr P.; Han, Gang; Ren, Dong
Abstract: A new basal horntail wasp, Cretosirex xiaoi gen. et sp. nov., in the family Siricidae is described from one fossil specimen collected from the Lower Cretaceous Yixian Formation in northeastern China. The new genus is placed in the basal group of Siricidae based on the forewing with 2r-m present and 1-RS subvertical; presence of the clearly subbasal anal loop; lacking of a corrugated forewing membrane and presence of the transmesonotal suture. It shares several intermingled characters with the three extinct subfamilies of Siricidae, but the new genus cannot be attributed to any of these three subfamilies. Our new discovery expands the distribution range of Siricidae fossil records and emphasizes the need for more studies of this major insect lineage in the Mesozoic deposits.